“Sapu Cantik” Innovation (Healthy, Safe, and Caring for Our Prospective Brides) as an Effort to Increase Motivation for Catin Health Visits - M. Suhron; Siti Safitri Mulita; Hasinuddin (Universitas STRADA Indonesia, 2024)
Health service visits are decreasing at the Primary Health Care level, including a decrease in premarital couple visits. This innovation aims to provide support and cross-sector cooperation in increasing health visits for couples before marriage. The implementation method in developing this innovation is to use the Research and Development design, which has 2 stages of activity. The first stage is to evaluate a couple's premarital visit through field studies using documents, interviews, and observations and determine strategic issues. The results show that the number of premarital couple visits has not reached 100% and is not optimal. This Sapu Cantik Innovation provides solutions for premarital couples as a form of cross-sectoral concern for the health of premarital couples. This innovation hopes to help and identify premarital couples who face health problems before, during, and after marriage to improve family health.